2021
DOI: 10.1186/s12935-021-02108-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and integrative analysis of ACLY and related gene panels associated with immune microenvironment reveal prognostic significance in hepatocellular carcinoma

Abstract: Background Cumulating evidence reveals the key role of aberrant lipogenesis and immunogenomic features in hepatocellular carcinoma (HCC). However, there are still obstacles in our understanding of the complicated interaction between metabolic reprogramming and tumor immune microenvironment. Methods We compared metabolomic, transcriptomic and immunogenomic characteristics of portal vein tumor thrombosis (PVTT) and primary tumor to seek valuable mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Currently, although many researchers have established numerous prognostic models for HCC, [29][30][31] there is no prognostic model related to SGMGs to systematically predict and evaluate the overall prognosis of HCC patients. Therefore, to reveal the potential function and unique prognostic value of SGMGs in HCC, we examined public datasets through bioinformatics analysis to provide new insights for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, although many researchers have established numerous prognostic models for HCC, [29][30][31] there is no prognostic model related to SGMGs to systematically predict and evaluate the overall prognosis of HCC patients. Therefore, to reveal the potential function and unique prognostic value of SGMGs in HCC, we examined public datasets through bioinformatics analysis to provide new insights for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al [35] have stated that TNFRSF4 is strongly associated with the immune microenvironment of HCC and contributes to poor prognosis. CD276 is a potential target for HCC immunotherapy and can be utilized as a predictor of survival in HCC patients [36] , [37] , [38] . It indicated that the prognostic model we constructed provided potential therapeutic targets and prognostic assessment indicators for immunotherapy of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of ACLY inhibitor and programmed death ligand 1 antibody largely inhibits chemically induced hepatocarcinogenesis; [66] ACLY can regulate the canonical Wnt pathway by affecting the stability of β-catenin; [67] ONECUT2-FGF2-ACLY axis regulates metastasis of hepatocellular carcinoma; [65] Bioinformatics analysis shows that ACLY is significantly correlated with immune checkpoint CD276 and immune cell infiltration; [68] Downregulation of ACLY can reverse sorafenib resistance, and targeting ACLY can effectively treat drug-resistant hepatocellular carcinoma [69] Malignant tumors of the head and neck ACLY plays a key role in oral carcinogenesis; [70] ACLY affects DNA damage repair, and ACLY expression can predict the efficacy of radiotherapy for head and neck squamous cell carcinoma; [71] Long non-coding RNA TINCR can bind ACLY to protect it from ubiquitination degradation, thereby maintaining the level of acetyl-CoA, promoting the progression of nasopharyngeal carcinoma and chemotherapy resistance…”
Section: Cancermentioning
confidence: 99%